Minimizing physical habitat impacts at downstream of diversion dams by a multiobjective optimization of environmental flow regime. (June 2021) - Sedighkia, Mahdi; Datta, Bithin; Abdoli, Asghar
Abstract: Present study links physical habitat simulation with the irrigation loss function to assess optimal environmental flow regime. The main motivation is Lack of optimization framework in the structure of reliable environmental flow methods such as physical habitat simulation. Data-driven model was used to simulate physical habitats. Moreover, a multi objective particle swarm optimization was utilized to optimize environmental flow regime by considering two objective functions including weighted useable area function and normalized benefit function for irrigation demand. Based on results, physical habitat data-driven model was robust to assess habitat suitability. Moreover, proposed multi objective optimization model is able to assess environmental flow properly. In the case study, physical habitat impact was minimized to 30% that means 70% of useable habitats would be protected. In contrast, 60% of maximum requested water demand would be supplied which implies a fair balance between demand and environmental flow.